2005
DOI: 10.1143/jjap.44.4339
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Study of Machinable Ceramic over Temperature Range from Room Temperature to 1000°C

Abstract: m e anisotropy of the inelastic mean free path (m) for electrons with energies behveen -1&lOWeV has been studied for the tint time in Re@, NaWOg and Ti0 crystals. The MFP was calculated within the one-plasmon and local density approximations from the imaginary part of the complex energy-dependent exchange and comlation potential of the Hedin-Lundqvist type. It is shown thal the MFP in compounds with a highly anisotmpic elecvon density distribution. such as ReOS and NaWOI, differs in various crystallographic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Wang et al 14) and Nishimura et al 15) studied the relationship between temperature and surface acoustic wave velocity. Kashiwagura et al 16) reported the temperature dependence of bulk waves. Matsuda et al 17) reported the measurement of a uniform temperature by a laser ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 14) and Nishimura et al 15) studied the relationship between temperature and surface acoustic wave velocity. Kashiwagura et al 16) reported the temperature dependence of bulk waves. Matsuda et al 17) reported the measurement of a uniform temperature by a laser ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the advantages of ultrasonic measurements such as noninvasiveness and faster response, some works on the application of ultrasound to temperature estimations have been carried out extensively. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In the early stages, Degertekin et al 1) carried out temperature measurements of semiconductor wafers using Lamb waves, and Simon et al 2) attempted to fabricate a temperature tomograph using an array sensor. Mizutani and coworkers, 4,14) Kudo and coworkers, 7,9) Huang et al, 6) Tsai et al, 10) Funakoshi et al, 17) and Minamide et al 16) extensively studied on the measurements of temperature distributions in air using multiple sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 8) and Nishimura et al 11) studied on the relationship between temperature and surface acoustic wave velocity. Kashiwagura et al 13) reported on the temperature dependence of bulk waves. Ito et al 15) reported on the relationship between the attenuation of a longitudinal wave and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Because of advantages of ultrasonic measurements, such as noninvasive and faster time response, several studies on the temperature measurements by ultrasound have been made extensively. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In our previous works, 13,14) an ultrasonic pulse echo method with an inverse analysis was developed and applied to the measurements of internal temperature distributions of heated thick plates. In our previous work, 14) the practical feasibility of the ultrasonic inverse method coupled with a one-dimensional finite difference calculation was successfully demonstrated through an experiment with a steel plate of 30 mm thickness whose single side was heated by contact with molten aluminum at 700 C. It should be noted that the internal temperature distribution can be determined from the transit time of a longitudinal wave propagating through the thick plate.…”
Section: Introductionmentioning
confidence: 99%